PENGARUH PDB RIIL DAN VARIABEL FISKAL TERHADAP PENANAMAN MODAL ASING LANGSUNG DI INDONESIA (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
This study aims to determine the influence of Real GDP and fiscal variables for foreign direct investment in Indonesia in period 1980 to 2006, and also to determine the level of sensitivity (elasticity) of foreign direct investment to GDP Real and fiscal variables in Indonesia in 1980 to 2006. The data used in this study is time series data or annual data for 27 years secondary. Data obtained from Statistics Economics and Finance Indonesia (SEKI) BI. The research method used a model with a Multiple Linear Regression analysis: analysis of correlation (R), the analysis of the coefficient of determination (R2), the elasticity analysis, and test the stability of the model, while the tests performed were F test, t test, and test autocorrelation with Durbin Watson and multicollinearity test using Eviews program. From the results of this study showed that 96.16% of foreign direct investment in Indonesia is influenced by real GDP, income tax, property tax, sales tax, economic development spending, government spending on transport and communications, government spending on education, as well as the economic crisis while the rest of 3.84 % influenced by other factors outside the model. Effect of Real GDP, PBB, government spending on transport and communications and in partial dummy variable is not significant while the Income Tax, sales tax, government spending for education and development are significant on direct foreign investment in Indonesia from 1980 to 2006.